The simple macroeconomics of fiscal austerity: Public debt,deficits and deficit caps - Thomas I. Palley (Intervention. European Journal of Economics and Economic Policies, 2012)
This paper explores the macroeconomics of fiscal austerity. A binding budget deficit cap makes the economy more volatile by turning the government budget into an automatic destabilizer. Public debt helps maintain aggregate demand (AD) in the presence of a lower price level because a lower price level increases the real value of public interest payments and also has a positive wealth effect. That makes public debt significantly different from private debt. If the economy is subject to a binding deficit cap public debt may no longer stabilize output. This is because increased real interest payments may be matched by spending cuts, giving rise to a negative balanced budget multiplier.
Keywords: E12; E60; E62; H62; 330; fiscal austerity; budget deficit cap; public debt; lower price level